Awareness of Forensic Odontology among Dentists in Pakistan and its Impact on Dental Record Keeping - Fizza Tahir, Hina Zafar Raja, Muhammad Nasir Saleem, Ayesha Iqbal, Muhammad Saad Ullah, Faiqua Yasser, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Forensic odontology (FO) has an important role to play in the field of forensic science to gather evidence for human identification. Dental records form an integral component of forensic evidence in this regard. Dental practitioners need to be aware of the legal significance of dental record keeping. They should be able to provide accurate information on which forensic evidence can be based. Aim: To assess the awareness regarding FO and dental record-keeping practices amongst dental partitioners in Pakistan. Methods: A cross-sectional study was conducted among dental practitioners to assess the awareness regarding FO and dental record-keeping in clinical practice. Results: A total of 380 responses were received. Results showed that only 2% of the respondents studied the subject of forensic dentistry at the undergraduate or postgraduate level. 88 % of the individuals were interested in receiving formal training in forensic dentistry and 96% recommended the subject of forensic dentistry to be introduced as a separate postgraduate training program in Pakistan. More than half of the respondents reported a lack of record-keeping in their clinical practice. Conclusions: Limited awareness was observed regarding FO among dental practitioners in Pakistan primarily due to lack of exposure to the subject. In terms of dental record keeping, a limited number of practitioners in our study reported adhering to it. Hence, there is a need to develop measures to promote awareness and knowledge about FO and dental record management in Pakistan. Keywords: Forensic odontology, awareness, education, dental records, dental identification.